Structural behavior evaluation of precast slabs prototypes made with tire rubber residue concrete - Trigo, Ana Paula Moreno (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
A significant part of concrete produced in Brazil is used to make columns, beams and slabs in building structures. Considering that the inclusion of residues in the concrete can produce a reduction of the structural element strength, and, considering that the roof slab usually does not demand higher actions than the floor slab, it is possible to partially replace the concrete aggregate for economically and ecologically materials. The aim of this work is to present a recycling alternative for tire rubber from retreading process, using it as part of the concrete aggregate in roof slabs. Two unidirectional slab prototypes with lattice joist were tested to the flexure. One of them had some tire rubber residue and the other had not. Vertical displacements and concrete and reinforcement strains were measured with comparing clocks and electric strain gages, respectively. Based on these results and on the kind of the slab collapse, a structural analysis was made. It was observed that the addition of the rubber residue does not make impracticable its technical use and presents advantages for the environmental aspect, though it is structurally less efficient and leads to a higher cement consumption.